Gestão de componentes alternativos para o processo de manufatura de produtos eletroeletrônicos - Lara, Alexandre (2018)
The present work seeks to demonstrate a study on a management project for the purchase and use of electronic components, mechanics, fixation and or identification as an alternative option in electronic projects. The study used lean manufacturing tools (Lean Manufacturing) as an example of VSM (Value Stream Mapping), Brainstorming, analyzing its applicability, viability and the benefits achieved through them. The proposed improvement of the activities covered helps to understand their role in the processes involved in the production of a company. For this, a case study was made in a company located in the southern region of Brazil, denominated simply as Company X. The Lean Manufacturing system can be considered a very important tool in achieving continuous results through the optimization of processes and consequently causes that the objectives be met in a more satisfactory manner, not only regarding the end of the procedure, but also how it was achieved, and especially its permanence with the process of continuous improvement.